2019
DOI: 10.5222/buchd.2019.46320
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Ophthalmology Consultations of Inpatients In A Tertiary Pediatric Hospital

Abstract: Sonuç olarak, gözün primer hastalıkları kadar, sistemik hastalıklara sekonder göz tutulumları da olabilmektedir. Kronik hastalığı olan hastalarda başlangıçta göz bulguları olmasa bile ilerleyen dönemlerde gelişebilecek tutulumları saptamak açısından düzenli göz muayenesinin yapılması önemlidir.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 11 publications
(11 reference statements)
1
4
0
Order By: Relevance
“…In our study, we observed that most patients were consulted for rule out. This was consistent with other studies as well (13)(14)(15). In our study, the most common reason for consultation in the rule-out group was headache.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…In our study, we observed that most patients were consulted for rule out. This was consistent with other studies as well (13)(14)(15). In our study, the most common reason for consultation in the rule-out group was headache.…”
Section: Discussionsupporting
confidence: 94%
“…Papilledema was detected in 17.1% of these children. In other studies, the rule-out group's most common reason for consultation was eye screening for systemic diseases (13)(14)(15). This difference may be due to the size of the hospital's pediatric service and the inclusion of only inpatients in other studies.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations